2023
DOI: 10.1002/ohn.162
|View full text |Cite
|
Sign up to set email alerts
|

Audiometric and Patient‐Reported Outcomes in Single‐Sided Deafness Cochlear Implant Recipients Using the CIQOL‐35

Abstract: Objective. Describe the effect that cochlear implantation (CI) has on audiometric outcomes and quality of life (QOL) in patients with single-sided deafness (SSD).Study Design. Retrospective case review.Setting. Tertiary university hospital system.Methods. Preoperative and postoperative AzBio performance and Cochlear Implant Quality of Life-35 (CIQOL-35) Profile scores in CI patients with SSD were compared, and postoperative measures were compared to those from CI patients without SSD.Results. Seventeen patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…One study by McRackan et al (17) showed very weak positive correlations between the CIQOL-35 domain scores and AzBio in quiet scores even when controlling for various demographic and audiometric factors. Recent studies by Mitton et al and Tolisano et al (11,18) on patients with single-sided deafness also did not find significant relationships between the global subdomain of CIQOL-35 (equivalent to the CIQOL-10) and speech recognition outcomes and between the change in CIQOL-35 subdomains scores and change in speech recognition scores.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…One study by McRackan et al (17) showed very weak positive correlations between the CIQOL-35 domain scores and AzBio in quiet scores even when controlling for various demographic and audiometric factors. Recent studies by Mitton et al and Tolisano et al (11,18) on patients with single-sided deafness also did not find significant relationships between the global subdomain of CIQOL-35 (equivalent to the CIQOL-10) and speech recognition outcomes and between the change in CIQOL-35 subdomains scores and change in speech recognition scores.…”
Section: Discussionmentioning
confidence: 86%
“…These questionnaires differed from other commonly used PROMs as they were developed using focus groups of CI patients and with thorough psychometric analysis. A few studies have investigated the association between speech recognition outcomes and quality of life as assessed by the CIQOL-35 or CIQOL-10 but have shown conflicting results (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Our results demonstrate clear benefit of CI in terms of QOL among all CI patients. CI centers around the US are reporting promising findings in regard to PROMs using the CIQOL-35 (7,12,14,15). Walia et al (7) and McRackan et al ( 14) demonstrated significant benefit among all CIQOL-35 domains, whereas Mitton et al (12) revealed significant QOL improvement among entertainment, listening effort, social, and global domains for single-sided deafness patients.…”
Section: Discussionmentioning
confidence: 99%
“…CI centers around the US are reporting promising findings in regard to PROMs using the CIQOL-35 (7,12,14,15). Walia et al (7) and McRackan et al ( 14) demonstrated significant benefit among all CIQOL-35 domains, whereas Mitton et al (12) revealed significant QOL improvement among entertainment, listening effort, social, and global domains for single-sided deafness patients. Our study shows a marked improvement in all QOL domains among a heterogenous CI population, which solidifies that all CI patients can reasonably expect positive change in QOL and increases the generalizability of PROMs using the CIQOL-35.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation